The Twitter (X) Ban in Pakistan: Digital Censorship and Its Effect on Democracy - Fatima Ahmad; Dr. Zameer Ahmed (Social Science Review Archives, 2025)
This study looks at how the Twitter (X) ban in Pakistan affects digital control and what it means for democracy. Using information from journalists, politicians, community leaders, and scholars, the research investigates how the ban has impacted freedom of speech, political expression, and community involvement. The study looks at how the government is gaining more control over online platforms by using national security as an excuse. It focuses on the idea of Digital Authoritarianism and the Digital Public Space. The findings show that many people believe the ban is a political move to silence opposing views. Even with these limits, people showed they could adapt by using VPNs and other platforms. People don't have much trust in government institutions to protect their online rights. The research highlights the important need for clear rules and legal protections to support democracy online.